Proteínas cry6 modificadas de bacillus thuringiensis para controle de nematoides - AARON T. WOOSLEY; KENNETH E. NARVA; TIMOTHY D. HEY (2015)
The subject invention concerns plants protected from nematode feeding damage and improved versions of Cry proteins. The subject invention also concerns improved versions of Cry6A proteins. Synthetic genes encoding these modified proteins are also part of the subject invention. Another embodiment of the subject invention includes plants transformed with the genes of the subject invention. In yet another embodiment the subject invention concerns Bt proteins for in-plant protection against crop damage by root knot nematode (RKN; Meloidogyne incognita) and soybean cyst nematode (SCN; Heterodera glycines).